Early Gastrointestinal Cancers - Otto, Florian; Lutz, Manfred P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This Recent Results in Cancer Research volume contains the majority of the invited expert contributions from the First St. Gallen EORTC Gastrointestinal Cancer Conference, held on 22-24 March 2012 in St. Gallen, Switzerland. Written by some of the world$1 (Bs leading experts in the field, the volume constitutes a comprehensive update on recent developments in the imaging, molecular biology, pathology, and multidisciplinary management of early cancer of the gastrointestinal tract. The latest recommendations regarding diagnosis and treatment are provided, and areas of consensus and controversy, identified. While the principal focus is on esophageal and gastric cancer, advances in the treatment of colorectal and pancreatic cancer are also discussed in some detail. This book will be of interest to every clinician involved in the care of patients with gastrointestinal malignancies.s
Keywords: Medicine; Radiology, Medical; Radiotherapy; Gastroenterology; Oncology; Cancer -- Surgery; Pathology; Medicine & Public Health; Oncology; Surgical Oncology; Radiotherapy; Gastroenterology; Pathology; Imaging / Radiology